Figurative Expressions of Romantic Infatuation In Sabrina Carpenter’s Songs - Saraswati, Kadek Trisna Ariesta; Skolastika, I Made Perdana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the use of figurative language expressing romantic infatuation in selected songs by Sabrina Carpenter. It employs a descriptive qualitative method and applies Knickerbocker and Reninger’s (1974) theoretical framework to examine six types of figurative language: simile, metaphor, personification, hyperbole, irony, and symbol. The study aims to analyze how these figurative elements function semantically to convey emotional depth and thematic meaning, particularly in relation to romantic infatuation. The data were obtained from purposively selected song lyrics based on their emotional relevance. The findings reveal 25 figurative expressions in total, with metaphor being the most frequently used, followed by hyperbole, simile, symbol, personification, and irony. Functionally, these expressions are primarily used to depict emotional pain, intensify feelings, express longing, and evoke personal memories. These results indicate that Sabrina Carpenter’s lyrics utilize figurative language as a meaningful semantic tool to express complex emotional experiences, especially those connected to romantic feelings and vulnerability.